Improving Reading Aloud Skills Using Komakas Media in Grade III Students of Nyama Christian Elementary School, Southwest Maluku Regency - Porloy, Pratiwi; Sahetapy, Sarah; Johansz, Dovila (Universitas Pattimura, 2025)
This study aims to improve reading aloud skills through the use of KOMAKAS media among third-grade students at SD Kristen Nyama, Maluku Barat Daya Regency. The research employed a classroom action research design, conducted in two cycles. The subjects of the study were 10 third-grade students. Each cycle consisted of planning, action, observation, and reflection stages. The results indicated an improvement in students’ reading aloud abilities. In the first cycle, the average score was 65.3, which increased to 80.3 in the second cycle after improvements were made in the teaching process. Therefore, the use of KOMAKAS media proved effective in enhancing the reading aloud skills of third-grade students at SD Kristen Nyama.